Обзор докладов Второй Международной конференции «Корпоративное управление и устойчивое развитие бизнеса: стратегические роли советов директоров». Блок «Корпоративная социальная ответственность» - Алекс Сеттлз Мэттью (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
We couldn’t even imagine 10 year ago corporate governance issues to become so popular in Russia as they are now. Today academia and professionals from business organize regular meetings and round tables to discuss research results, future directions for development and potential ways to overcome existing problems. It seems that corporate social responsibility concept will have similar history. It is clear now that question of building an effective stakeholder relations system become more and more popular. This review will be devoted to major findings and points of presentations with topics related to new evolving era of socially responsible corporations in Russia and worldwide